Evaluation of two types of seedling in broccoli (Brassica olerácea L.), in three localities of the muniotality of Pasto - Eraso J., Claudia; Romo B, David; Torres M, Francisco (Revista de Ciencias Agrícolas, 2011)
The study was conducted in three municipality of Pasto, in order to perform a technical and economic comparison for the production of seedlings of broccoli seed in two types, the traditional (soil) and the technical system (greenhouse). We used an unrestricted random design in a 3 x 2 factorial arrangement, the factor A corresponded to three locations (Botana, Buesaquillo and SENA), and factor B, two types of seed (Traditional and modernized) with three replicates and the results were interpreted by analysis of variance and Duncan for the variables: percentage of emergence, days to emergence and percentage of seedlings useful and economically analyzed for the two seed. Of the treatments, the seedlings tech showed better results, with higher percentage of emergency in the three locations, with averages of 98% to 95.3%. The averages presented traditional nursery of 85.5%, 69.42% and 59.42% for Buesaquillo, Botana and SENA respectively. Days to emergence in the seedbed technical no significant differences between locations, with values between 6 and 4.67 days, contrary to the nursery where they presented traditional values (11, 13.6 and 17), to Buesaquillo, SENA and Botana. As a percentage of useful plants, there were significant differences in the type of seed, with superior tech average with 94.8% compared to 67.25% traditional. The economic analysis determined that the tech seedlings showed a better performance, as profitability was 37.9%, as total costs for production were lower, as opposed to traditional hotbed, leaving a profit of 5.7% . With these benefits the producer may return on investments in traditional seedbed ($600,000) and the technical system ($3,300,500) to the sixth cycle of production.